Remix e fotografia : manifestações do remix nas montagens de fotolivros com templates - Magni, Lolita Fernanda (2016)
This study considers the concept of Remix Culture as a way to develop new ways of dealing with images in our contemporary context. From a communicational approach, we observe the relationship between Remix and photography through photo books assemblages in softwares using ready-made templates in order to understand how the Remix manifest itself through these dynamics. Our theoretical foundation is composed mainly of concepts of Remix and Remix Culture, from the ideas of Eduardo Navas, Lev Manovich and Lawrence Lessig. In order to understand photography’s place in the contemporary world and the human’s relationship to the images, we use Vilém Flusser’s contribution. With the purpose of discussing the photography metamorphoses in the Remix process, we use the concept of Aura, by Walter Benjamin (1985), and Allegory, by Craig Owens (2004). The Software Studies perspective (MANOVICH, 2013; FULLER, 2008), in turn, contributes to the construction of the proposed methodology, which unfolds in the analysis proposing four basic axes: the first one unveils the issue of the template, in order to understand what is their role in these assemblies and their relationship with the Remix actions. We understand that, while the system of templates and their easy-to-use nature simplifies the assembly process, this very autonomy confiscates from the user his authorial emancipation from the photo book. In the second axis, we unfold Navas (2012) Remix categories, in order to check what kinds of Remix can manifest themselves through different construction possibilities in our object, identifying the presence of two of the four categories proposed by the author. In the third axis, we make an observation about the profile of users of this kind of softwares, trying to identify how they behave in relation to the Remix possibilities and, as a result, we perceived three different types of users, from the passive one to a more active one in the handlings. In the fourth and last axis, we analyze how we can delineate the authorship in these software constructed assemblages, and we could verify that the software is able to invade the user’s creating space, blurring the boundaries of authorship in these dynamics.